Effect of the Cathodic Gas Diffusion Layer on the Performance of a Proton Exchange Membrane Electrolyzer - Daniela Lorena Canelas Montaño; Pablo Ruiz García; Andrés Jerez Navarro; Modesto Aguirre Gomez; José Javier López Cascales (Energies)
Hydrogen production through electrolysis using renewable resources is highly promising for reducing greenhouse gas emissions. While significant efforts have focused on developing more efficient and cost-effective catalysts to lower hydrogen production costs, catalysts are not the primary expense in electrolyzer fabrication. In the case of Proton Exchange Membrane Water Electrolyzers (PEMWEs), other components—such as the proton membrane, gas diffusion layer (GDL), and bipolar plates—contribute more to overall costs. To explore this, a study was conducted on the performance of PEMWEs with various carbon paper GDLs, developed in the lab, on the cathodic side. This study examined how properties like electrical conductivity, porosity, and gas permeability affect performance. These findings emphasize the need to optimize components beyond catalysts to improve the cost-effectiveness of hydrogen production through electrolysis.